2021
DOI: 10.1002/adfm.202010513
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Extraction of Schottky Barrier Height and Universality of Fermi Level De‐Pinning of van der Waals Contacts

Abstract: Due to Fermi level pinning (FLP), metal‐semiconductor contact interfaces result in a Schottky barrier height (SBH), which is usually difficult to tune. This makes it challenging to efficiently inject both electrons and holes using the same metal—an essential requirement for several applications, including light‐emitting devices and complementary logic. Interestingly, modulating the SBH in the Schottky–Mott limit of de‐pinned van der Waals (vdW) contacts becomes possible. However, accurate extraction of the SBH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Weak interlayer interaction leads to mild orbital overlap and interface dipole between two neighbored 2D materials, which can further suppress FLP. [107] Le Quang et al have observed a rigid shift of 120 meV between the scanning tunneling spectra of TMD at contact interfaces to monolayer and bilayer graphene. The shift equals to their work function difference, indicating that Fermi level at the contact is mostly depinned.…”
Section: Transferred 2d Contactsmentioning
confidence: 99%
“…Weak interlayer interaction leads to mild orbital overlap and interface dipole between two neighbored 2D materials, which can further suppress FLP. [107] Le Quang et al have observed a rigid shift of 120 meV between the scanning tunneling spectra of TMD at contact interfaces to monolayer and bilayer graphene. The shift equals to their work function difference, indicating that Fermi level at the contact is mostly depinned.…”
Section: Transferred 2d Contactsmentioning
confidence: 99%
“…This result indicates that Cl–SnSe 2 forms a nearly ideal interface with WSe 2 without pinning and thus largely follows the Schottky–Mott rule ( S = 1); this S value is comparable to the values obtained using the transferred metal, [ 8 ] 1T‐WTe 2 , [ 32 ] and degenerately n‐doped SnSe 2 . [ 18 ] Such a near‐ideal interface was further verified by the enhanced subthreshold swing (SS) value and minimal hysteresis, which are strongly related to the interfacial contamination (Figure S14, Supporting Information). [ 33,39,40 ] The schematics of the band diagrams are shown in Figure S15, Supporting Information, depicting the cases of evaporated metal and Cl–SnSe 2 contacts, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…[ 8,14 ] However, the approach suffers from poor atmospheric contamination, and requires an inert‐gas processing environment, which hence increases the fabrication complexity. On the other hand, recently, the use of vdW 2D metals as contacts has been shown to provide atomically clean interfaces at metal–semiconductor junctions; [ 15–18 ] these clean interfaces from vdW 2D metals could potentially prevent Fermi‐level pinning, thus promising excellent control over the Schottky barrier and the resulting device polarity. Several attempts have been made to use 2D metals as vdW contacts on various 2D semiconductors, such as highly p‐doped WSe 2 , [ 15 ] NbSe 2 , [ 16 ] 1T‐TaS 2 , [ 17 ] and degenerately doped semiconducting SnSe 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-doping side (V g < 0 V) shows three distinct features (Figure 1b and c), namely, neutral bright exciton (χ 0 ), positive trion (χ + ), and positively charged biexciton (β + ). Due to the relative positions of the Fermi levels between 1L-WS 2 and graphene, it is more difficult to inject holes than electrons [32]. Thus it is challenging to dope the 1L-WS 2 flake strongly ptype, as suggested by the sustained χ 0 peak intensity even at high negative V g (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%